Sulfide solid electrolyte, preparation method thereof and battery
By dissolving lithium sulfide and lithium halide in anhydrous organic solvent and sintering with phosphorus sulfide, the problem of difficult mixing of high-melting point raw material particles is solved, and a high-performance sulfide solid electrolyte is prepared, which significantly improves its ionic conductivity and stability.
Patent Information
- Application Number
- CN202411395182.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-14
AI Technical Summary
In the prior art, the particle size of high melting point raw materials is large and it is difficult to mix uniformly, making it difficult for solid electrolytes to form pure phases, affecting performance.
Lithium sulfide and lithium halide are dissolved in anhydrous organic solvent, mixed with phosphorus sulfide after drying, sintering treatment, and prepared sulfide solid electrolyte, avoiding the problems of raw material refinement and poor mixing uniformity.
The uniform mixing of high melting point raw materials is achieved, the ionic conductivity and batch stability of the solid electrolyte are improved, and the prepared sulfide solid electrolyte is free of impurities, which significantly improves the conductivity.
Smart Images

Figure CN119306192A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy batteries, and in particular to a sulfide solid electrolyte, a preparation method thereof, and a battery. Background Art
[0002] The key to the healthy development of new energy vehicles is the power battery. At this stage, technicians are constantly improving the performance of power batteries in terms of processes, materials, etc., but it is still a liquid electrolyte system. From a safety perspective, organic liquid lithium-ion batteries have great safety hazards due to the use of volatile, low-flash-point organic solvents. In addition, the energy density of liquid batteries is close to the upper limit. When using a high-nickel positive electrode and a silicon-based negative electrode system, 350Wh / kg may be close to the limit energy density of liquid lithium-ion batteries, and technical iteration and upgrading are urgently needed. Solid-state batteries can adapt to higher-capacity positive and negative electrode materials, and the energy density can reach 500Wh / kg. The range of electric vehicles equipped with solid-state batteries will easily reach 1,000km. All-solid-state lithium-ion batteries have both higher safety and greater room for improvement in energy density, which can provide support for the full popularization of new energy vehicles.
[0003] Unlike traditional liquid lithium-ion batteries, the electrolyte of solid-state batteries exists in the form of solids (solid electrolytes) in the electrodes, which has the advantages of non-volatility, non-combustion and fast ion conduction. At present, solid electrolyte materials used in solid-state batteries are mainly divided into the following types: oxides, sulfides, polymers and halide solid electrolytes. Among them, sulfides have better ionic conductivity than the other three solid electrolytes, and their texture is softer and more processable, and they have been widely studied. In the laboratory preparation process, high-energy ball milling process is often used to prepare sulfide electrolytes, but this method is difficult to mass produce on a large scale. Therefore, the use of a simple mixing method has made the mass production of sulfide electrolytes see the dawn. However, in actual operation, the problem of difficult mixing is often faced, which makes it difficult for the prepared solid electrolyte to form a pure phase, which in turn affects the performance of use.
[0004] In order to solve these problems, the existing technology reduces the particle size of the raw materials to achieve uniformity of the mixture. However, in actual application, further refinement of the raw materials increases the process and poses a huge challenge to the refinement equipment, and it is still difficult to solve the problem of poor uniformity of the mixture after refinement. Therefore, it is urgent to develop a method for preparing argyrodite-type sulfide solid electrolyte to improve the uniformity of the raw material mixture. Summary of the invention
[0005] In view of this, the present invention is committed to providing a sulfide solid electrolyte and a preparation method and a battery thereof, so as to solve the problem in the prior art that the high melting point raw material particles have large particle size and are difficult to mix uniformly.
[0006] In order to solve the above technical problems, this application is implemented as follows:
[0007] A first aspect of the present invention provides a method for preparing a sulfide solid electrolyte, the preparation method comprising the following steps:
[0008] S1. Dissolving lithium sulfide and lithium halide in an anhydrous organic solvent to obtain a first material; drying the first material to obtain a first mixture;
[0009] S2, mixing the first mixture with phosphorus sulfide to obtain a precursor;
[0010] S3, sintering the precursor.
[0011] Optionally, the molar ratio of the lithium sulfide to the lithium halide is 1:(0.75-2.5); the mass ratio of the lithium halide to the anhydrous organic solvent is (0.15-0.30):1; the mass ratio of the lithium sulfide to the anhydrous organic solvent is (0.30-0.43):1.
[0012] Optionally, the molar ratio of the phosphorus sulfide to the first mixture is (7-14):1.
[0013] Optionally, the lithium halide is selected from at least one of lithium bromide, lithium chloride, lithium iodide and lithium fluoride.
[0014] Optionally, the phosphorus sulfide is selected from P 2 S 3 , P 2 S 5 , P 4 S 4 , P 4 S 7 , P 4 S 9 and P 4 S 6 At least one of .
[0015] Optionally, the preparation method further comprises: contacting the organic solvent with the activated molecular sieve for dehydration treatment to obtain an anhydrous organic solvent; optionally, the organic solvent is selected from at least one of ethanol, ethylene glycol, isopropanol, n-butanol, acetonitrile and tetrahydrofuran.
[0016] Optionally, in step S1, the drying treatment is vacuum drying; the conditions of the vacuum drying include: temperature of 80 to 120°C, vacuum degree of -0.1 to -0.085 MPa, and time of 5 to 10 hours.
[0017] Optionally, in step S3, the sintering treatment is performed in an inert atmosphere, and the conditions of the sintering treatment include: a temperature of 350 to 560° C. and a time of 5 to 20 hours.
[0018] A second aspect of the present invention provides a sulfide solid electrolyte, which is prepared according to the above method.
[0019] A third aspect of the present invention provides a battery, which includes a solid electrolyte, wherein the solid electrolyte includes the sulfide solid electrolyte prepared by the above method and / or the above sulfide solid electrolyte.
[0020] Through the above technical scheme, the beneficial technical effects of the present invention are as follows: the method of the present invention dissolves lithium sulfide and lithium halide in an anhydrous organic solvent to obtain a first material, dries the first material to obtain a first mixture, and achieves uniform mixing of high-melting-point raw materials; obtains a precursor by mixing the first mixture with phosphorus sulfide; and sinters the precursor to obtain a solid electrolyte with excellent quality. The preparation method of the sulfide solid electrolyte of the present invention is simple and efficient, with low preparation cost, can achieve uniform mixing of high-melting-point raw materials, and then achieve uniform mixing of precursors. The solid electrolyte prepared by the method of the present invention has no impurities, significantly improved ionic conductivity, and high batch stability.
[0021] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention, but do not constitute a limitation of the present invention.
[0023] Figure 1 Shown is the XRD pattern of the sulfide solid electrolyte prepared in Example 1.
[0024] Figure 2 Shown is the XRD pattern of the sulfide solid electrolyte prepared in Example 2.
[0025] Figure 3 Shown is the XRD pattern of the sulfide solid electrolyte prepared in Example 3.
[0026] Figure 4 Shown is the XRD pattern of the sulfide solid electrolyte prepared in Comparative Example 1.
[0027] Figure 5 Shown is the XRD pattern of the sulfide solid electrolyte prepared in Comparative Example 2. DETAILED DESCRIPTION
[0028] The present invention discloses a sulfide solid electrolyte and a preparation method and a battery. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0029] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0030] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0031] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0032] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0033] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0034] In order to solve the problem in the prior art that the particle size of the high melting point raw material is large, it is difficult to mix the materials evenly, and the uneven mixing of the high melting point raw material will lead to the generation of impurities in the prepared solid electrolyte, the present invention adopts the following technical solution:
[0035] A first aspect of the present invention provides a method for preparing a sulfide solid electrolyte, the preparation method comprising the following steps:
[0036] S1. Dissolving lithium sulfide and lithium halide in an anhydrous organic solvent to obtain a first material; drying the first material to obtain a first mixture;
[0037] S2, mixing the first mixture with phosphorus sulfide to obtain a precursor;
[0038] S3, sintering the precursor.
[0039] The preparation method of the sulfide solid electrolyte of the present invention does not need to refine the raw materials, reduces the solid electrolyte preparation process, and obtains uniformly dispersed raw materials by dissolving high melting point raw materials lithium sulfide and lithium halide in an anhydrous organic solvent in proportion, thereby promoting reaction uniformity, facilitating the formation of a pure phase, and thereby improving the ionic conductivity of the solid electrolyte. The method of using raw materials dissolved in an anhydrous organic solvent can avoid the problem of poor stability of the synthesis batch due to differences in raw material particle size.
[0040] In the present invention, the molar ratio of lithium halide, lithium sulfide and phosphorus sulfide added can satisfy Li 6-x PS 5-x A 1+x , wherein A is selected from at least one of Cl, Br, I and F, and 0≤x≤1.
[0041] According to the present invention, the molar ratio of the lithium sulfide to the lithium halide may be 1:(0.75-2.5). Exemplarily, the molar ratio of the lithium sulfide to the lithium halide may be any value among 1:0.75, 1:1, 1:1.25, 1:1.5, 1:1.75, 1:2, 1:2.25 and 1:2.5 or any value within the range consisting of any two of the above values.
[0042] In the present invention, the mass ratio of the lithium halide to the anhydrous organic solvent may be (0.15-0.30):1. Exemplarily, the mass ratio of the lithium halide to the anhydrous organic solvent may be any one of 0.15:1, 0.2:1, 0.25:1 and 0.30:1 or any value within the range of any two of the above values. The mass ratio of the lithium sulfide to the anhydrous organic solvent may be (0.30-0.43):1. Exemplarily, the mass ratio of the lithium sulfide to the anhydrous organic solvent may be any one of 0.30:1, 0.32:1, 0.35:1, 0.40:1 and 0.43:1 or any value within the range of any two of the above values.
[0043] According to the present invention, the molar ratio of the phosphorus sulfide to the first mixture may be (7-14): 1. Exemplarily, the molar ratio of the phosphorus sulfide to the first mixture may be any one of 7:1, 8:1, 10:1, 12:1 and 14:1 or any value within the range of any two of the above values.
[0044] According to the present invention, the lithium halide can be selected from at least one of lithium bromide, lithium chloride, lithium iodide and lithium fluoride. The physical state of the lithium halide in the present invention can be crystal or powder. As a preferred embodiment, the water content of the lithium halide in the present invention is ≤0.3wt%; the purity of the lithium halide is ≥99wt%.
[0045] According to the present invention, the phosphorus sulfide can be selected from P 2 S 3 , P 2 S 5 , P 4 S 4 , P 4 S 7 , P 4 S 9 and P 4 S 6 At least one of .
[0046] The D50 of the lithium sulfide in the present invention is not specifically limited. Exemplarily, the D50 of the lithium sulfide is ≤30 μm.
[0047] According to the present invention, the preparation method may further include: contacting the organic solvent with the activated molecular sieve for dehydration treatment to obtain an anhydrous organic solvent.
[0048] Exemplarily, the organic solvent may be selected from at least one of ethanol, ethylene glycol, isopropanol, n-butanol, acetonitrile and tetrahydrofuran. Preferably, the organic solvent is ethanol.
[0049] The activated molecular sieve used in the present invention can be at least one of an activated 3A molecular sieve, an activated 4A molecular sieve, and an activated 5A molecular sieve, wherein the activation step of the molecular sieve can be well known to those skilled in the art, for example, it can be a 3A molecular sieve. The water content in the anhydrous organic solvent obtained by dehydrating the organic solvent in the present invention is preferably less than 50ppm.
[0050] According to the present invention, in step S1, the drying process may be vacuum drying; the conditions of the vacuum drying may include: a temperature of 80 to 120°C, a vacuum degree of -0.1 to -0.085 MPa, and a time of 5 to 10 hours, preferably, a time of 8 to 10 hours.
[0051] According to the present invention, in step S2, the mixing process may be any mixing method of the first mixture with phosphorus sulfide. Exemplarily, the mixing process may be mechanical mixing.
[0052] According to the present invention, in step S3, the sintering treatment can be carried out in an inert atmosphere, and the inert atmosphere can be nitrogen and / or argon; the conditions of the sintering treatment may include: a temperature of 350 to 560°C, preferably a sintering temperature of 420 to 500°C; a time of 5 to 20 hours, preferably, a time of 5 to 10 hours.
[0053] The preparation method of the present invention may further include: crushing the material obtained by sintering to obtain a sulfide solid electrolyte with a target particle size.
[0054] A second aspect of the present invention provides a sulfide solid electrolyte, which is prepared according to the above method.
[0055] A third aspect of the present invention provides a battery, which includes a solid electrolyte, wherein the solid electrolyte includes the sulfide solid electrolyte prepared by the above method and / or the above sulfide solid electrolyte.
[0056] The present invention is further described in detail by way of examples. The raw materials used in the examples can be obtained through commercial sources. The density of anhydrous ethanol used in each example of the present invention is 0.7893 kg / m 3 .
[0057] Example 1
[0058] (1) The activated molecular sieve is placed in anhydrous ethanol for dehydration treatment, wherein the mass of the activated molecular sieve is 1 kg, the volume of the anhydrous ethanol is 5 L, and the dehydration treatment time is 40 h, ensuring that the water content in the anhydrous ethanol after the dehydration treatment is less than 50 ppm.
[0059] (2) Weigh 298.0287 g of lithium sulfide, 144.7046 g of lithium chloride, and 177.8853 g of lithium bromide, dissolve them in dehydrated anhydrous ethanol, and stir for 30 min to obtain a first material. The obtained first material is placed in a vacuum oven for drying at a temperature of 60° C. for 10 h, and the vacuum degree of the vacuum oven is -0.1 MPa to obtain a first mixture.
[0060] (3) The first mixture was mechanically mixed with 379.3812 g of phosphorus pentasulfide at a rotation speed of 20,000 rpm for 1 min to obtain a precursor.
[0061] (4) The precursor was sintered in a sintering furnace filled with nitrogen at a sintering temperature of 450°C, a sintering time of 15 h, and a heating rate of 5°C / min to obtain a sintered sample.
[0062] (5) The sintered sample was crushed to obtain the sulfide solid electrolyte Li with a D50 of 13 μm in this embodiment. 5.4 PS 4.4 ClBr 0.6 The XRD pattern of the sulfide solid electrolyte is as follows: Figure 1 shown.
[0063] Example 2
[0064] (1) The activated molecular sieve is placed in anhydrous ethanol for dehydration treatment, wherein the mass of the activated molecular sieve is 1 kg, the volume of the anhydrous ethanol is 5 L, the dehydration treatment time is 40 h, and the water content in the anhydrous ethanol after the dehydration treatment is ensured to be less than 50 ppm.
[0065] (2) Weigh 327.8812 g of lithium sulfide and 254.7231 g of lithium chloride and dissolve them in the above dehydrated ethanol, and stir for 30 min to obtain a first material. The obtained first material is placed in a vacuum oven for drying at a temperature of 60° C. for 10 h and a vacuum degree of -0.1 MPa to obtain a first mixture.
[0066] (3) The first mixture was mechanically mixed with 417.3897 g of phosphorus pentasulfide at a rotation speed of 20,000 rpm for 1 min to obtain a precursor.
[0067] (4) The precursor was sintered in a sintering furnace filled with nitrogen at a sintering temperature of 500°C, a sintering time of 10 h, and a heating rate of 5°C / min to obtain a sintered sample.
[0068] (5) The sintered sample is processed to obtain a sulfide solid electrolyte Li with a D50 of 15 μm in this embodiment. 5.4 PS 4.4 Cl 1.6 The XRD pattern of the sulfide solid electrolyte is as follows: Figure 2 shown.
[0069] Example 3
[0070] (1) The activated molecular sieve is placed in anhydrous ethanol for dehydration treatment, wherein the mass of the activated molecular sieve is 1 kg, the volume of the anhydrous ethanol is 5 L, the dehydration treatment time is 40 h, and the water content in the anhydrous ethanol after the dehydration treatment is ensured to be less than 50 ppm.
[0071] (2) Weigh 278.4553 g of lithium sulfide, 142.7121 g of lithium chloride, and 204.6752 g of lithium bromide, dissolve them in dehydrated anhydrous ethanol, and stir for 30 min to obtain a first material. The obtained first material is placed in a vacuum oven for drying at a temperature of 60° C. for 10 h, and the vacuum degree of the vacuum oven is -0.085 MPa to obtain a first mixture.
[0072] (3) The first mixture was mechanically mixed with 374.1572 g of phosphorus pentasulfide at a rotation speed of 20,000 rpm for 1 min to obtain a precursor.
[0073] (4) The precursor was sintered in a sintering furnace filled with nitrogen at a sintering temperature of 440°C, a sintering time of 14 h, and a heating rate of 5°C / min to obtain a sintered sample.
[0074] (5) The sintered sample was crushed to obtain the sulfide solid electrolyte Li with a D50 of 13 μm in this embodiment. 5.3 PS 4.3 ClBr 0.7 The XRD pattern of the sulfide solid electrolyte is as follows: Figure 3 shown.
[0075] Comparative Example 1
[0076] (1) Weigh 278.4553 g of lithium sulfide, 142.7211 g of lithium chloride, 204.6752 g of lithium bromide, and 374.1572 g of phosphorus pentasulfide, and mix them mechanically at a speed of 20,000 rpm for 1 min to obtain a precursor.
[0077] (2) The precursor was sintered in a sintering furnace filled with nitrogen at a sintering temperature of 440°C, a sintering time of 14 h, and a heating rate of 5°C / min to obtain a sintered sample.
[0078] (3) The sintered sample was crushed to obtain a sulfide solid electrolyte Li with a D50 of 13 μm in this comparative example. 5.3 PS 4.3 ClBr 0.7 The XRD pattern of the sulfide solid electrolyte is as follows: Figure 4 shown.
[0079] Comparative Example 2
[0080] (1) Weigh 327.8812 g of lithium sulfide, 254.7231 g of lithium chloride, and 417.3897 g of phosphorus pentasulfide and mix them mechanically at a speed of 20,000 rpm for 1 min to obtain a precursor.
[0081] (2) The precursor was sintered in a sintering furnace filled with nitrogen at a sintering temperature of 500°C, a sintering time of 10 h, and a heating rate of 5°C / min to obtain a sintered sample.
[0082] (3) The sintered sample is crushed to obtain the sulfide solid electrolyte Li with a D50 of 15 μm in this embodiment. 5.4 PS 4.4 Cl 1.6 The XRD pattern of the sulfide solid electrolyte is as follows: Figure 5 shown.
[0083] Test Example 1
[0084] The sulfide solid electrolytes prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were tested for ionic conductivity. The ionic conductivity test method was as follows: the solid electrolytes prepared in Examples / Comparative Examples were tested in a glove box filled with an inert atmosphere.
[0085] The obtained powder samples were subjected to uniaxial pressing to produce sheets with a diameter of 10 mm and a thickness of about 2 to 3 mm at 200 MPa. The ionic conductivity was measured by the AC impedance method at room temperature (25°C) using an electrochemical workstation and a measurement frequency of 1 Hz to 7 MHz. The test results are shown in Table 1.
[0086] The sulfide solid electrolytes prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were analyzed by XRD patterns. Figures 1 to 5 .
[0087] Table 1
[0088] Group Ionic conductivity (mS / cm) Example 1 10.5 Example 2 9.5 Example 3 12 Comparative Example 1 8 Comparative Example 2 7.5
[0089] It can be seen from Table 1 that the ionic conductivity of the sulfide solid electrolyte prepared by the method of the present invention is significantly improved. By performing XRD pattern analysis on the sulfide solid electrolytes prepared in the examples and comparative examples, it can be seen that the sulfide solid electrolytes in Examples 1 and 3 have no impurity phase, while the sulfide solid electrolytes in Comparative Examples 1 and 2 have impurity phases.
[0090] The XRD results of Example 1, Example 2 and Example 3 correspond to Figure 1 , Figure 2 , Figure 3 ,from Figure 1 , Figure 2 , Figure 3It can be seen that by premixing the two high melting point raw materials in an organic solvent to achieve uniform mixing of the raw materials, the sintered sulfide solid electrolyte presents a single argyrodite peak, with no impurity peaks at around 2θ=29°, 34°, and 35°, and thus has high ionic conductivity. However, in Comparative Examples 1 and 2, the three raw materials are simply mixed, and the uniform dispersion of the raw materials cannot be achieved, and the XRD spectrum of the sintered sulfide solid electrolyte is ( Figure 4 , Figure 5 ) shows the characteristic peaks of argyrodite, but there are also peaks of other impurities (around 2θ=29°, 34°, and 35°), which is attributed to the uneven mixing of raw materials, showing that the solid electrolyte ion conductivity is low.
[0091] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a sulfide solid electrolyte, characterized in that: The preparation method comprises the following steps: S1. Dissolving lithium sulfide and lithium halide in an anhydrous organic solvent to obtain a first material; drying the first material to obtain a first mixture; S2, mixing the first mixture with phosphorus sulfide to obtain a precursor; S3, sintering the precursor.
2. The preparation method according to claim 1, characterized in that: The molar ratio of the lithium sulfide to the lithium halide is 1:(0.75-2.5); The mass ratio of the lithium halide to the anhydrous organic solvent is (0.15-0.30):1; the mass ratio of the lithium sulfide to the anhydrous organic solvent is (0.30-0.43):
1.
3. The preparation method according to claim 1, characterized in that: The molar ratio of the phosphorus sulfide to the first mixture is (7-14):
1.
4. The preparation method according to claim 1, characterized in that: The lithium halide is selected from at least one of lithium bromide, lithium chloride, lithium iodide and lithium fluoride.
5. The preparation method according to claim 1, characterized in that: The phosphorus sulfide is selected from at least one of P2S3, P2S5, P4S4, P4S7, P4S9 and P4S6.
6. The preparation method according to claim 1, characterized in that: The preparation method further comprises: contacting the organic solvent with the activated molecular sieve for dehydration treatment to obtain the anhydrous organic solvent; Optionally, the organic solvent is selected from at least one of ethanol, ethylene glycol, isopropanol, n-butanol, acetonitrile and tetrahydrofuran.
7. The preparation method according to claim 1, characterized in that: In step S1, the drying treatment is vacuum drying; the conditions of the vacuum drying include: temperature of 80 to 120°C, vacuum degree of -0.1 to -0.085 MPa, and time of 5 to 10 hours.
8. The preparation method according to claim 1, characterized in that: In step S3, the sintering process is performed in an inert atmosphere, and the conditions of the sintering process include: a temperature of 350 to 560° C. and a time of 5 to 20 hours.
9. A sulfide solid electrolyte, characterized in that: The sulfide solid electrolyte is prepared according to the method according to any one of claims 1 to 8.
10. A battery, characterized in that: The battery comprises a solid electrolyte, wherein the solid electrolyte comprises a sulfide solid electrolyte prepared by the method according to any one of claims 1 to 8 and / or a sulfide solid electrolyte according to claim 9.
Citation Information
Cited By
Preparation method of pure-phase sulfide solid-state electrolyte, solid-state electrolyte and solid-state battery
CN119370812A
Preparation method of lithium tin phosphorus sulfur solid-state battery
CN120341399A